Development and Validation of a Teacher Competency Assessment Instrument Using Confirmatory Factor Analysis - Mukti, Taufiq Satria; Noviafitri, Kartika Satya; Arianti, Putri Dwi (FKIP Universitas Lampung, 2025)
Abstract: Development and Testing of Teacher Competency Assessment Instruments with CFA (Confirmatory Factor Analysis) and Profiles of State Madrasah Teachers. Objective: The study was conducted with the aim of producing a teacher competency measurement instrument in accordance with valid and reliable standards. This needs to be done because the instruments currently used do not have empirical evidence, the instruments are very long, and are not yet practical. This study also aims to provide an overview of the competency of teachers involved as research objects. Methods: The study was conducted on 124 state madrasah teachers at MAN 1 Malang, MAN 2 Malang, MAN Kota Batu, MTs N 2 Malang, MTs N 3 Malang, and madrasahs in Batu City, namely MTs N Kota Batu and MAN Kota Batu. The study was conducted by developing an instrument that was tested with CFA to obtain empirical evidence in the form of instrument validity and reliability. Finding: The results showed that the developed instrument met the goodness of fit criteria with an RMSEA index of 0.110; CI 0.0937 - 0.126; and CFI 0.926. The results of the study showed a very good instrument quality with a reliability of 0.950. The tested instrument was then used to measure teacher competency in madrasahs. The results show that teachers have 51.75% professional ability, 44.88% pedagogical ability, 44.46% social ability, and 66.56% personality. The majority of teachers' work experience is more than 10 years as much as 62.99% with the same percentage for teachers with educator certification. Conclusion: From this study it can be concluded that teacher competence needs to be measured periodically as a form of performance evaluation. The results of teacher competency evaluation are the basis for mapping and planning teacher competency improvement programs that will be visible to institutions and individual teachers so that they are able to present quality learning for students. Keywords: assessment instrument, teacher competence, CFA, reliability.